Implementation of 'Character Month' as an Innovation to Shape a Generation with Great Character - Putri, Sekar Destina; Zainuddin, Almuntaqo (ELSE (Elementary School Education Journal): Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to describe the implementation of the character month program as a form of school innovation in shaping the character of students, as well as to examine in depth the obstacles that arise in the implementation of character month at the School. The research method used is qualitative with an ethnographic approach. Data collection techniques in this study were designed with participatory observation and structured interviews. The object of this research specifically focuses on aspects related to the character month program, including strategies, impact on students, and reviewing the extent of involvement of all parties in charge of running the character month program. The research subjects are the head of Muhammadiyah Elementary School Kottabarat Special Program, teachers, students, and parents and the research system includes primary and secondary data. The collected data will later be analyzed using the Miles & Huberman analysis technique. The results of this study are 1) the implementation of character month is implemented through learning and extracurricular activities to instill and create students with ulul albab character, not only intelligent but also have an Islamic personality; 2) There are several obstacles that occur during the implementation of character month that need to be evaluated more deeply, such as the lack of understanding and commitment of school parties, time constraints, unstructured evaluation, and rapid policy changes that disrupt the continuity of character month. Keywords: Learning innovation; Character Month; Elementary School; Character Generation